BIODIVERSITY OF FISH FAMILY OSPHRONEMIDAE IN SWAMP WATERS IN BAGAN BILAH VILLAGE, DISTRICT OF PANAI TENGAH LABUHANBATU REGENCY - Yayuk Astriani; Khairul Khairul (BIOEDUKASI, 2022)
One of the swamp waters is located in Bagan Bilah Village, Panai Tengah District, Labuhanbatu Regency, North Sumatra Province. These swamp waters store a lot of fish diversity that has been used by the surrounding community. Among them are fish from the Osphronemidae family. This study aims to determine the biodiversity of fish of the Osphronemidae family in the swamp waters of Bagan Bilah Village. Fish sampling was carried out for 3 months, starting from October to December 2021. Fish are caught using traditional fishing gear called tangkol. The caught fish are collected, counted in number and then identified by species. The research data is calculated for its ecological index using the 2010 version of the Microsoft Excel application, then the data is displayed in tabular form. Based on the results of this study obtained 5 species of fish family Osphronemidae (Belontia hasselti, Betta imbellis, Trichogaster trichopterus, Trichopodus pectoralis, and Trichopsis vittatus). The Diversity Index (H') of Station 1 (0.78), Station 2 (0.76), and Station 3 (1.26). Uniformity Index (E) for Station 1 (0.43), Station 2 (0.42), and Station 3 (0.70). Dominance Index (C) for Station 1 (0.13), Station 2 (0.16), and Station 3 (0.28).